2011
DOI: 10.7150/ijbs.7.1161
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Helps Improve Photosynthesis and Carbohydrate Metabolism in Leaves of Muskmelon

Abstract: The most important quality for muskmelon (Cucumis melo L.) is their sweetness which is closely related to the soluble sugars content. Leaves are the main photosynthetic organs in plants and thus the source of sugar accumulation in fruits since sugars are translocated from leaves to fruits. The effects of grafting muskmelon on two different inter-specific (Cucurbita maxima×C. moschata) rootstocks was investigated with respect to photosynthesis and carbohydrate metabolism. Grafting Zhongmi1 muskmelon on RibenStr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 40 publications
7
25
0
1
Order By: Relevance
“…However, this decrease is up to 50% higher in plants that are not grafted and are under stress conditions due to high concentrations of NaCl; the same authors [38], found an inverse linear correlation of the photosynthetic activity with respect to the concentration of Na + and Cl-in leaves, attributing the excess of these to a disorder in the photosynthetic apparatus; similar studies witnessed the same photosynthetic activities [39,40]. Under normal conditions (without stress), grafted plants behave in a similar way to previous studies; in the case of Amaro et al [41], observed that the grafting of the cucumber plants increased the stomatal conductance and photosynthetic capacity of the plant compared to those that had not been grafted; Similar results were reported by Liu et al [42], attributing this increase in photosynthetic capacity to an increase in the amount of chlorophyll a and b in plants; additionally they reported the increase in carbohydrate accumulation in fruit, due to the activity of two key enzymes for this process in melon plants; Similar results were presented by QI et al [43] and González et al [44], in melon and citrus respectively. Likewise, Qinghai Gao et al [45], Suggest that grafted plants have the ability to better use Cl under stress conditions, as well as presenting a better photosynthetic ef iciency compared to those plants that were not grafted, this higher photosynthetic ef iciency may be due to the fact that high levels of Cl decrease the transpiration of the leaves, improving the ef iciency of water use in photosynthesis [46].…”
Section: Stomatal Conductance and Co 2 Assimilationsupporting
confidence: 78%
“…However, this decrease is up to 50% higher in plants that are not grafted and are under stress conditions due to high concentrations of NaCl; the same authors [38], found an inverse linear correlation of the photosynthetic activity with respect to the concentration of Na + and Cl-in leaves, attributing the excess of these to a disorder in the photosynthetic apparatus; similar studies witnessed the same photosynthetic activities [39,40]. Under normal conditions (without stress), grafted plants behave in a similar way to previous studies; in the case of Amaro et al [41], observed that the grafting of the cucumber plants increased the stomatal conductance and photosynthetic capacity of the plant compared to those that had not been grafted; Similar results were reported by Liu et al [42], attributing this increase in photosynthetic capacity to an increase in the amount of chlorophyll a and b in plants; additionally they reported the increase in carbohydrate accumulation in fruit, due to the activity of two key enzymes for this process in melon plants; Similar results were presented by QI et al [43] and González et al [44], in melon and citrus respectively. Likewise, Qinghai Gao et al [45], Suggest that grafted plants have the ability to better use Cl under stress conditions, as well as presenting a better photosynthetic ef iciency compared to those plants that were not grafted, this higher photosynthetic ef iciency may be due to the fact that high levels of Cl decrease the transpiration of the leaves, improving the ef iciency of water use in photosynthesis [46].…”
Section: Stomatal Conductance and Co 2 Assimilationsupporting
confidence: 78%
“…content (Liu et al, 2011). Although we did not measure leaf area and other growth parameters in the field experiment, our results from the greenhouse experiments suggested the improved total leaf area, root length, and root surface area might be important contributing factors to the increased fruit size of grafted watermelon in the field trial.…”
Section: Resultsmentioning
confidence: 82%
“…To do this, plants require to enhance their capacity to assimilate inorganic N, which was verified in a previous study where the activity of nitrate reductase was shown to increase in tomato leaves exposed to higher light intensities [31]. Several studies in cereal crops [32][33][34] and muskmelon [35] report a positive correlation between chlorophyll content and NUtE. Our results show no changes in chlorophyll content under different NUE values, in agreement with some reports in grafted Solanaceae crops, such as tomato or bell pepper [36,37].…”
Section: Nue and Developmental Stagementioning
confidence: 84%